Karakteristik dan Sifat Tepung Singkong Termodifikasi (Mocaf) dan Manfaatnya pada Produk Pangan - Novian Wely Asmoro (Journal of Food and Agricultural Product, 2021)
ABSTRACTCassava (Manihot esculenta crantz) has a carbohydrate content of 34%, which is one of the potential commodities in Indonesia. Widely, cassava is used by the people of Indonesia as a staple food and can be processed directly into various local food products. Modern modification of cassava flour currently uses technology that includes physical, chemical or microbiological modifications. Mocaf (Modified Cassava Flour) is a modification of cassava flour using a fermentation technique. The modification process of cassava flour aims to change the characteristics of the flour produced. Changes in the characteristics of the modified cassava flour mocaf encourage its use to become more varied. The stages of making mocaf flour are: cutting / slicing cassava into chips with a thickness ranging from 0.5-1 cm, soaking and fermenting, draining and drying, and the final stage of milling / flouring. The fermentation process is an important process in making mocaf, fermentation involves microbes from both bacteria and fungi. One of the bacteria that is widely used is lactic acid bacteria (LAB) species Lactobacillus plantarum. The fermentation process lasts for 36-72 hours, resulting in an increase in the protein content of mocaf flour. The results obtained by substitution of mocaf flour to wheat flour in wet bread and noodle products ranged from 20%-40%, for cookies products it could reach 100%. Keywords: Fermentation, Mocaf, Cassava